Problem Based Module Development as Preparation for Selection of Science Olympicers in Biology Field - Latipah, Rina April; Iswari, Retno Sri; Bintari, Siti Harnina (Universitas Negeri Semarang)
The National Science Olympic (OSN) is a prestigious event in the world of education organized by the Ministry of Education and Culture ( Kemendikbud ). OSN is implemented with the aim of facilitating and motivating students who have talent in the field of science, so that they can improve their abilities and select students to the international level . The good achievements of Indonesian sons and daughters in academia provide promising Human Resources (HR) solutions. However few students are aware of and interested to participate and compete with other academic institutions at national level even in the midst of international. The module is a supporting medium for the preparation of the selection of candidates for the regency level high school science olympic participants. The development of a question-based module for high school biology olympic is expected to improve school human resources to involve students in various national and international competitions. The results showed that